Improving the Academic Performance and Mental Health of Non-Traditional University Students Through a Shorter Delivery Model : Exploring the Impact of the Southern Cross Model. - Nieuwoudt, Johanna (Student Success v.14 n.1 p.35-46 https://doi.org/10.5204/ssj.2660, 2023)
University students are often depicted as carefree young adults; however, many students struggle to manage the "normal" stresses of university life and may experience high rates of psychological distress. This study compared a traditional delivery model to a shorter delivery model (i.e., the Southern Cross Model) in terms of students' psychological distress, their perceived time pressure, and academic performance. The results indicated a significant difference in academic performance and psychological distress between the shorter delivery model and the traditional delivery model, with students in this shorter delivery model experiencing lower levels of psychological distress and enhanced academic performance. No significant difference in time pressure was found between the delivery models. This study indicates that the Southern Cross Model may enhance students' academic performance and help them to better manage the normal stresses of university life. [Author abstract]